Calcite alabaster artifacts from Hierapolis in Phrygia, Turkey: Provenance determination using carbon and oxygen stable isotopes. Issue 2 (5th December 2018) - Scardozzi, Giuseppe; Brilli, Mauro; Giustini, Francesca
Abstract: Alabastro fiorito or listato, a vividly colored and strongly patterned carbonate stone, is widely diffused in the ancient city of Hierapolis in Phrygia (Turkey) as building material. This stone, also known as Hierapolis alabaster, was extensively quarried in antiquity in the territory near the city. Numerous ancient quarries of the Hierapolis alabaster were documented in previous studies in sites immediately around the city and also about 13 km northwest of Hierapolis, near Gölemezli. Carbon and oxygen stable isotopes and X‐ray diffraction (XRD) analysis were used to investigate the possibility to discriminate different quarries or different geographically coherent extraction areas; these techniques were also applied to analyze alabaster artifacts from some monuments of Hierapolis as a case study. The data show that carbon and oxygen isotopes may be effective at distinguishing between the quarries of Gölemezli and Hierapolis, and allow for attribution of unknown alabaster artifacts to one of these areas. The possibility to identify the provenance of unknown alabasters from the different extraction sites or geographically coherent extraction areas near Hierapolis using isotopes only is difficult; in some cases XRD analysis to detect aragonite versus calcite may improve the discrimination among Hierapolitan quarries and contribute to the assignment procedure.